A Critical Taxonomy of the Theories About the Paths into the Reduction - Perkins, Patricio Agustín (2017)
The paths or ways to the transcendental reduction are a pivotal phenomenological notion in Husserl’s philosophy. The metaphor of path, in fact, alludes to the demonstrative proofs of transcendental phenomenology. Nonetheless, Husserlian scholarship has not yet been able to end the disputes surrounding this topic, and as a result, competing interpretations continue to prevail. Since existing theories about the paths have not yet been cataloged or analyzed in their global context, I intend to classify the main existing theories about the paths and evaluate the trend established by Iso Kern. Thus, this paper answers the following questions: how many kinds of theories about the paths are there? And, how plausible is the trend and approach initiated by Kern? In order to evaluate each theory, I will compare the interpretation with its exemplary cases. The key contribution of this investigation is therefore twofold: to distinguish with unequivocal concepts the two main trends of hermeneutical theories in play and to evaluate the plausibility of the aforementioned Kernian one. The paper also attempts to show that the hermeneutical approach initiated by Kern has no contextual examples for its conceptual scheme and should consequently be abandoned in favor of an alternative solution.